Analysis of Human Resource Development Strategies Using the Balanced Scorecard (BSC) Method in the Perum Perumnas Apartment Samesta Sentraland Medan Project - Mauliza Syafhira Rahmah; Prihatin Lumbanraja; Zulkarnain Zulkarnain (Majapahit Journal of Islamic Finance and Management, 2025)
This study analyzes human resource (HR) development strategies at the Samesta Sentraland Medan Apartment Project, identifies factors influencing competency development, and proposes a Balanced Scorecard (BSC)-based HR management model emphasizing the Learning and Growth perspective to enhance employee performance and project effectiveness. A qualitative descriptive approach was applied through in-depth interviews with project leaders and staff, field observations, and document analysis. The research utilized the BSC framework, focusing on technical competence, soft skills, career development, and knowledge management, with data triangulation ensuring validity and reliability. Findings reveal that BSC integration fosters a structured, measurable, and comprehensive HR development system. Key strategies include tiered training, mentoring, internal and external programs, and KPI-based performance evaluations. Internal factors such as management commitment, organizational culture, and digital literacy, along with external aspects like regulations and labor availability, significantly influence strategy effectiveness. Overall, this approach enhances employee competence, collaboration, and productivity while aligning HR development with strategic project objectives.